(5x+4)+(9x+5)=

Simple and best practice solution for (5x+4)+(9x+5)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (5x+4)+(9x+5)= equation:


Simplifying
(5x + 4) + (9x + 5) = 0

Reorder the terms:
(4 + 5x) + (9x + 5) = 0

Remove parenthesis around (4 + 5x)
4 + 5x + (9x + 5) = 0

Reorder the terms:
4 + 5x + (5 + 9x) = 0

Remove parenthesis around (5 + 9x)
4 + 5x + 5 + 9x = 0

Reorder the terms:
4 + 5 + 5x + 9x = 0

Combine like terms: 4 + 5 = 9
9 + 5x + 9x = 0

Combine like terms: 5x + 9x = 14x
9 + 14x = 0

Solving
9 + 14x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 14x = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 14x = 0 + -9
14x = 0 + -9

Combine like terms: 0 + -9 = -9
14x = -9

Divide each side by '14'.
x = -0.6428571429

Simplifying
x = -0.6428571429

See similar equations:

| 4x+126+22=180 | | 2q+16-17q=-14-18q | | 8.50x+5=90 | | 4a(2a+6)= | | 3b+6=4b | | -26=-3k-8 | | -16+3t=2t | | 3n-2n=30 | | 6(y-5)-4=6(-4y+5)-6y | | 3(x+2)x=18 | | (-7+1)+(-x+2)= | | 0=10cos(3x) | | 5x^7/6=10 | | (4f-6)/4=1 | | -1=-8w+23 | | 9x+57+51=180 | | 9-4=-4w+6w | | 4g-7g+7=-g-5 | | (x+3)(x-8)=x^2-4x+24 | | 3p/8-15-33 | | 18x+14y+63z=5 | | -6can+2x-11=-2(2X-3)+4 | | 2s+8s=20 | | 0.04x+0.06(10000-x)=720 | | F(x)=50(6) | | a^2-4a+3a-12=0 | | -7u(u-7)=-4 | | -3n-8=9n+6 | | -2h=10 | | 3(k-4)-2(k+2)-14=-22 | | 19m=10 | | -4n+18=-3n-5 |

Equations solver categories